INTERDEPENDENCE OF ROLES, WORK-FAMILY ROLES AND PSYCHOLOGICAL STRAIN: A STUDY ON MARRIED WORKING WOMEN IN INDONESIA - farradinna, Syarifah (Faculty of Humanities, Diponegoro University, 2017)
Work–family balance issues have become more common in Indonesia, especially in Riau Province. Traditional structural and economic changes and affect how married women participate in the family and the workforce. Imbalance between work and family affects individual physical and psychological well-being. Psychological strain is caused by stresses such as depression, anxiety, anger, hostility, irritability, inability ethic, or lack of physical strains, and closely related symptoms of burnout. A random sampling of 178 married working women in the civil servant department participated in the study. Data analysis was done with using of descriptive statistics and inferential statistics by SPSS 21 and Excel software. Analyses showed WIF and FIW are consistently correlated with psychological strain (0.462, and 0.428, p < 0.001); however, WIF was positively correlated significantly with FIW (0.632, p < 0.001). Psychological strain was also positively correlated significantly with work–family conflict (0.493, p < 0.001) and negatively correlated with the interdependence of roles (-0.152, p < 0.005). The results showed that the majority of married working women experienced high levels of work interference from the family and low levels of family interference at work, with an average score on the variables psychological strain and interdependence of roles. The diversity of Indonesia allowed demographic analysis and comparisons between respondents.